GoldVariants, a resource for sharing rare genetic variants detected in bleeding, thrombotic, and platelet disorders: Communication from the ISTH SSC Subcommittee on Genomics in Thrombosis and Hemostasis. (5th August 2021) - Megy, Karyn; Downes, Kate; Morel‐Kopp, Marie‐Christine; Bastida, José M.; Brooks, Shannon; Bury, Loredana; Leinoe, Eva; Gomez, Keith; Morgan, Neil V.; Othman, Maha; Ouwehand, Willem H.; Perez Botero, Juliana; et al.
Abstract: The implementation of high‐throughput sequencing (HTS) technologies in research and diagnostic laboratories has linked many new genes to rare bleeding, thrombotic, and platelet disorders (BTPD), and revealed multiple genetic variants linked to those disorders, many of them being of uncertain pathogenicity when considering the accepted evidence (variant consequence, frequency in control datasets, number of reported patients, prediction models, and functional assays). The sequencing effort has also resulted in resources for gathering disease‐causing variants associated with specific genes, but for BTPD, such well‐curated databases exist only for a few genes. On the other hand, submissions by individuals or diagnostic laboratories to the variant database ClinVar are hampered by the lack of a submission process tailored to capture the specific features of hemostatic diseases. As we move toward the implementation of HTS in the diagnosis of BTPD, the Scientific and Standardization Committee for Genetics in Thrombosis and Haemostasis has developed and tested a REDCap‐based interface, aimed at the community, to submit curated genetic variants for diagnostic‐grade BTPD genes. Here, we describe the use of the interface and the initial submission of 821 variants from 30 different centers covering 14 countries. This open‐access variant resource will be shared with the community to improve variant classification and regular bulk data transfer to ClinVar.